Screening for Hypertension and Electrocardiography (ECG) for Cardiovascular Diseases Risk - Armalina, Desy; Witjahjo, Bambang; Susilaningsih, Neni; Purnawati, Ratna Damma; Ismail, Akhmad; Saktini, Fanti (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
ECG is a routine, accessible, inexpensive, and non-invasive tool for diagnosis of CVD and has been commonly described in medical reports as a suitable diagnostic tool for assessing ‘silent’ heart disease. An observational descriptive study, in Gisikdrono Urban Communities, found 72% elderly with hypertension, and higher than the reported national prevalence in 2013 (25.8%). We gained 38% of elderly with abnormal ECG which is: 5% Old myocardial infarction, 3% IMO Anteroseptal, 5% LVH, 8% LAD, 3%) of Inferior Ischemia, 3% dysrhythmia, and 13% bradycardia, without complaint of heart disease before. Aging became one of the factors of declining protection in the heart and increases the risk of destruction of heart failure. Considering examination of other organs that can affect the cause of heart anomalies to the elderly and expected to raise awareness of the importance of maintaining the blood pressure.